2012
DOI: 10.1128/jvi.01341-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Novel Variant Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) Strain: Evidence for Recombination between Vaccine and Wild-Type PRRSV Strains

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is the etiologic agent of porcine reproductive and respiratory syndrome (PRRS), which can evolve continuously by random mutation or intragenic recombination. Here we report the complete genomic sequence of a PRRSV variant with nucleotide acid deletions and insertions in the nonstructural protein 2 (nsp2) gene and a possible recombination event between a modified live virus (MLV) vaccine strain and a prototype Chinese field strain. P orcine reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 8 publications
1
44
0
3
Order By: Relevance
“…Recombination between wild-type and attenuated vaccine strains and the putative consequences thereof have been demonstrated and/or discussed for several viruses, such as members of the Flaviviridae family (34)(35)(36), pestiviruses (37), polioviruses (38)(39)(40), avian paramyxovirus-1 (41), myxoma viruses (42), porcine reproductive and respiratory syndrome virus (43), and herpesviruses (15,22,44,45). Recombination between two live herpesvirus vaccine strains was reported for pseudorabies virus, which is an alphaherpesvirus that infects pigs (44).…”
mentioning
confidence: 99%
“…Recombination between wild-type and attenuated vaccine strains and the putative consequences thereof have been demonstrated and/or discussed for several viruses, such as members of the Flaviviridae family (34)(35)(36), pestiviruses (37), polioviruses (38)(39)(40), avian paramyxovirus-1 (41), myxoma viruses (42), porcine reproductive and respiratory syndrome virus (43), and herpesviruses (15,22,44,45). Recombination between two live herpesvirus vaccine strains was reported for pseudorabies virus, which is an alphaherpesvirus that infects pigs (44).…”
mentioning
confidence: 99%
“…Field research has also proven that transmitted vaccine viruses may not share the same phenotype as the paternal attenuated strain and that may revert to virulence (10) . Further, natural recombination between the vaccine virus and field virus has been reported (53) .…”
Section: Control Y Prevenciónmentioning
confidence: 98%
“…The dead virus vaccine used in Europe is Hipra®Suipravac-PRRS in oil emulsion o/w as an adjuvant. It has been observed that the virus of the attenuated virus vaccines is able to replicate, revert to pathogenicity, cause viremia, shed and infect healthy susceptible animals (10,53) , while the inactivated virus vaccine although it does not replicate, nor does it produce viremias, cases of null protection have been reported (24) .…”
Section: Control Y Prevenciónmentioning
confidence: 99%
“…Bacteriology was quantified by culture and all bacteriological work, including setup, culture, identification, and typing, was done following standard operating procedures outlined in the manual of clinical microbiology. Testing for virology were carried out according to previously reported protocols [5,7]. All animal research was conducted under the guidance of the Centers for Disease Control and Prevention (CDC)'s Institutional Animal Care and use committee in an association for assessment and accreditation of laboratory animal care International accredited facility.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Porcine circovirus type 2 is the primary causative agent of porcine circovirus-associated diseases (PCVADs) in pigs and causes significant economic losses in most pig-producing countries. More recently, an outbreak of S. suis infection causing mortality in humans was caused by an emergent, highly virulent strain of S. suis, a pathogen that persists in the lungs of clinically healthy pigs [7,8]. Most infectious diseases are caused by bacteria which proliferate within quorum sensing (QS) mediated biofilms [9,10].…”
mentioning
confidence: 99%